Urgensitas Kebijakan Institutional Repository Perguruan Tinggi - Arienda Addis Prasetyo; Labibah Labibah; Marwiyah Marwiyah (ijd-demos, 2022)
AbstractInstitutional repository provides an opportunity for visitors to be able to access the collection or information owned by the library without having to come to the library. Through the institutional repository of the library helps promote the scientific publications produced by the academic community and business will be able to increase the number of citation from a publication. The management of scientific publications using the institutional repository is already contained in the Circular Letter of the Director general of higher education decree No. 152/E/T/2012 dated January 27, 2012 about the Publication of Scientific papers (S1, S2, and S3) and the Circular of the directorate of higher education No. 1864/E4/2015 dated 15 July 2015, concerning Credit Score Assessment  (PAK) (Lecturer must be able to be traced online).  But seeing the urgency the application or use of the institutional repository is not all institutions of higher education implement it. One of the only private high school in Yogyakarta . Interestingly the agency has not been applying the institutional repository.This study uses a case study research Methodology qualitative. A Single approach Grounded (embedded research), as a guide to conduct and determine the flow of the research. This research was conducted by direct interview, the main data Source in qualitative research are the words and actions of the informant is a librarian. However, to maintain the privacy and good name of the institution, the informant did not deign to mention the name of the college/ institution in the research. Results and discussion : 1) a Lot of Things That Should be Prepared; 2) the Limited Fulfillment of the Needs of Implementation; 3) the Demands On the Application of the Institutional Repository Conclusion : it is Necessary the presence of the ability of human resources management and technology resources and information as well as the commitment of the institution to the organization with the support of the entire academic community members in filling the content of institutional repository.  As well as his involvement the role of librarians as a profession that is in charge of going to this documentation.Keywords: College, Institutional Repository, Library, Librarian, Policy. AbstrakInstitutional repository memberikan peluang bagi pemustaka untuk dapat mengakses koleksi atau informasi yang dimiliki perpustakaan tanpa harus datang ke perpustakaan. Melalui institutional repository perpustakaan membantu mempromosikan publikasi ilmiah yang dihasilkan oleh sivitas akademika dan usaha ini akan mampu meningkatkan jumlah sitiran dari publikasi. Pengelolaan publikasi ilmiah dengan menggunakan institutional repository sudah termuat pada Surat Edaran Dirjen Dikti No. 152/E/T/2012 tanggal 27 Januari 2012 tentang Publikasi Karya Ilmiah (S1, S2, dan S3) dan Surat Edaran Dikti No 1864/E4/2015 tanggal 15 Oktober 2015 perihal Penilaian Angka Kredit (PAK) Dosen (harus dapat ditelusur secara online). Namun melihat urgensinya penerapan atau penggunaan institutional repository tersebut belum semuanya lembaga perguruan tinggi menerapkannya. Salah satunya sekolah tinggi swasta di Yogyakarta. Menariknya lembaga tersebut belum menerapakan institutional repository. Penelitian ini menggunakan  penelitian studi kasus dengan metodologi kualitatif. Pendekatan tunggal terpancang (embedded research), sebagai  pedoman   untuk   melakukan   dan   menentukan   alur   penelitian. Penelitian ini dilakukan secara wawancara langsung, sumber data utama dalam penelitian kualitatif ialah kata-kata dan tindakan dari informan yakni pustakawan. Namun untuk menjaga privasi dan nama baik institusinya, informan tidak berkenan untuk menyantumkan/menyebutkan nama perguruan tinggi/ institusinya dalam penelitan. Hasil dan pembahasan : 1) Banyak Hal Yang Harus Disiapkan; 2) Tuntutan Terhadap Penerapan Institutional Repository; 3) Terbatasnya Pemenuhan Kebutuhan Implementasi. Simpulan: Perlu adanya kemampuan pengelolaan sumber daya manusia dan sumber daya teknologi dan informasi serta komitmen institusi terhadap penyelenggaraan dengan dukungan seluruh komponen sivitas akademik dalam mengisi konten institutional repository.  Serta keterlibatannya peran pustakawan sebagai profesi yang membidangi akan hal dokumentasi.Kata kunci:  Institutional Repository, Kebijakan, Perpustakaan, Perguruan Tinggi, Pustakawan.